Vibration Response of Soil under Low-Frequency Vibration Using the Discrete Element Method - Lipengcheng Wan; Yonglei Li; Jinyu Song; Xiang Ma; Xiangqian Dong; Chao Zhang; Jiannong Song (Agriculture, 2023)
The vibration response of soil is a key property in the field of agricultural soil tillage. Vibration components of tillage machinery are generally used to reduce tillage resistance and improve work efficiency, and the pressure variation under low-frequency vibration will affect the fragmentation and dispersion of farmland soil. However, the gradient of pressure variation, frequency domain response, and effective transmission range is unclear. A new method based on the DEM (discrete element method) is presented to study the vibration response and pressure transmission under low-frequency vibration. Bench test results have shown that peak pressure positively correlates with the vibration frequency and attenuates rapidly at a vibration distance of 100 to 250 mm. The resulting data were also selected to determine the simulation model’s parameters. Amplitude, vibration frequency, and soil depth were used as test factors in single-factor simulation tests, and their effects on the peak pressure, frequency domain response, and effective transmission distance were analyzed. The results showed a positive relationship between the peak pressure and the test factors. The peak pressure increased with a maximum gradient of 19.02 kPa/mm at a vibration distance of 50 mm. The amplitude, vibration frequency, and soil depth positively correlated with the dominant frequency amplitude. The main frequency was independent of amplitude and soil depth. At a vibration distance of 250 mm, the dominant frequency was approximately twice the vibration frequency at 7–11 Hz and approximately equal to the vibration frequency at 13–15 Hz. Multiple exponential functions were used to fit the peak pressure attenuation function, obtaining an effective transmission distance range of 347.15 to 550.37 mm for the 5 kPa cut-off pressure. For a soil depth of 300 mm, the vertical shear wave diffusion angle was greater than the horizontal shear wave diffusion angle. This study clarifies the vibration response of soil under low-frequency vibration, which helps to design vibration-type, soil-engaging components of tillage machinery and match vibration parameters for energy-saving and resistance reduction purposes in soil tillage.